2000
DOI: 10.1001/archinte.160.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrence After Deep Vein Thrombosis and Pulmonary Embolism

Abstract: Venous thromboembolism recurs frequently, especially within the first 6 to 12 months, and continues to recur for at least 10 years after the initial VTE. Patients with VTE with neurologic disease and paresis or with malignant neoplasm are at increased risk for recurrence, while VTE patients with transient or reversible risk factors are at less risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
663
11
44

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,013 publications
(755 citation statements)
references
References 36 publications
37
663
11
44
Order By: Relevance
“…Long-term anticoagulant treatment is highly effective in preventing recurrent venous thromboembolism (VTE) in patients with idiopathic deep vein thrombosis (DVT) of the lower limbs [1][2][3] but is associated with an increased risk for major bleeding that may offset the benefits of anticoagulation [4]. Since the risk of recurrent VTE is believed to gradually diminish over time, many patients with idiopathic DVT may not require prolonged treatment with a vitamin K antagonist (VKA) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term anticoagulant treatment is highly effective in preventing recurrent venous thromboembolism (VTE) in patients with idiopathic deep vein thrombosis (DVT) of the lower limbs [1][2][3] but is associated with an increased risk for major bleeding that may offset the benefits of anticoagulation [4]. Since the risk of recurrent VTE is believed to gradually diminish over time, many patients with idiopathic DVT may not require prolonged treatment with a vitamin K antagonist (VKA) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…One study among patients >45 years age found that the 28-day case fatality rate after the first VTE event among all patients studied was 11%; among patients with cancer related VTE, it was 25% [3] . Approximately 30% patients with VTE may have recurrent events within 10 years [4] . The occurrence of VTE also results in substantial health care costs.…”
mentioning
confidence: 99%
“…Patients with malignant neoplasm who are complicated by thromboembolism are at increased risk for recurrence. 5 The indication, efficacy and safety of vena caval filters in the prevention of pulmonary embolism in patient with DVT is still controversial. 6,7 In the present case, platelet scintigraphy revealed the accumulation of platelets at the site of the filter, which suggested the growth of thrombus and a risk of recurrent pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%